The Impact of Literature for Indonesian Sustainable Tourism - Waode Surya Darmadali (Hasanuddin University, 2022)
Literature plays an important role in promoting sustainable tourism. Depicting the uniqueness of its culture and society with all the surroundings where literature grows, develops, and impacts. Literary Tourism established the relationship between literature and tourism where it illustrates a form of travel that occupy under the types of tourism, describing an instrument designed for the conservational purposes of specific category of cultural heritage such as the current case objectives, locations, events related to different aspects of literature. The purpose of this paper is to demonstrate the impact of literature for sustainable tourism in Indonesia. The method is used is exploratory qualitative research where it identifies existent resources of literature to foster Indonesian sustainable tourism through utilizing literature from various sources including media, website to obtain data related to literature, tourism, and tourist attraction. This paper offers an interdiciplinary approach that combines literary studies and tourism studies and the strong relation between literature and sustainable tourism and vice versa. Keywords: Literary tourism,sustainable, Indonesia, Culture, Society